Roads and jobs in Ethiopia - Matteo Fiorini; Marco Sanfilippo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
We look at how improving roads can affect jobs and structural transformation. We use a novel geocoded dataset covering the universe of Ethiopian roads and match this information with individual data to identify the effects of improvements in road infrastructure on the creation, quality, and sectoral distribution of jobs over the period 1994-2013. We find that, at the district level, higher market potential due to better roads contributes to the creation of new jobs, reduces the share of agricultural workers, and increases that of workers in the services sector but not in manufacturing. The latter experiences a relative increase in the share of informal workers. Finally, investigating the underlying mechanisms, we show that patterns of internal migration and changes in economic opportunities can help to rationalize our findings.
Keywords: L16; O18; O55; R4; 330; Ethiopia; roads; structural transformation; transport infrastructure